2008
DOI: 10.1002/ird.353
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hysteresis on three‐dimensional transient water flow during surface trickle irrigation

Abstract: The effect of hysteresis on deep percolation, irrigation efficiency and soil water content profiles by surface point sources was studied through the use of a cylindrical flow model which incorporates hysteresis in the soil water characteristic curve (Scott et al., 1983), evaporation from the soil surface and water extraction by roots. Several combinations of discharge rate and irrigation durations were tested. The dripper spacing was 60 Â 60 cm. The implementation of the mathematical model took place against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
(35 reference statements)
3
7
0
Order By: Relevance
“…In terms of the modelled cumulative volume of water through the bottom of the column (Figure 5), the volume predicted when using hysteretic SWCC was less than that predicted when using non-hysteretic SWCC, regardless of the upper surface boundary conditions. This result is consistent with the findings of Elmaloglou and Diamantopoulos (2008), who found that deep drainage under irrigation was reduced by soil moisture hysteretic effects. Analyses of model outputs indicate that lower drainage volumes occurred in hysteretic simulations because of: (1) higher evaporation rates in rainfall-evaporation simulations (HYDRUS evaporation is specified as a potential discharge, and actual evaporation is determined from a combination of potential evaporation and the soil moisture conditions), and (2) higher soil moisture contents and therefore higher total soil water storage (and hence less lower boundary discharge) in rainfall-redistribution simulations.…”
Section: Resultssupporting
confidence: 93%
“…In terms of the modelled cumulative volume of water through the bottom of the column (Figure 5), the volume predicted when using hysteretic SWCC was less than that predicted when using non-hysteretic SWCC, regardless of the upper surface boundary conditions. This result is consistent with the findings of Elmaloglou and Diamantopoulos (2008), who found that deep drainage under irrigation was reduced by soil moisture hysteretic effects. Analyses of model outputs indicate that lower drainage volumes occurred in hysteretic simulations because of: (1) higher evaporation rates in rainfall-evaporation simulations (HYDRUS evaporation is specified as a potential discharge, and actual evaporation is determined from a combination of potential evaporation and the soil moisture conditions), and (2) higher soil moisture contents and therefore higher total soil water storage (and hence less lower boundary discharge) in rainfall-redistribution simulations.…”
Section: Resultssupporting
confidence: 93%
“…Both the water retention and hydraulic conductivity curves show hysteresis as a function of the pressure head. Moreover, hysteresis can significantly influence water flow in variably saturated porous media (Vachaud and Thony, 1971; Gillham et al, 1979; Elmaloglou and Diamantopoulos, 2008). The majority of the studies (and models) concerning hysteresis in the unsaturated zone deal with static experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This model is used in the well‐known models, SWAP (Van Dam et al ., ), Hydrus 1D (Šimůnek et al ., ) and Hydrus 2D/3D (Šimůnek et al ., ). Elmaloglou and Diamantopoulos () explained in detail the incorporation of hysteresis in the mathematical model. It was assumed that a d = a w /2 where a w and a d are the a parameter in the relationship of van Genuchten () for the main wetting and drying curve, as proposed by Kool and Parker ().…”
Section: Methodsmentioning
confidence: 99%